Evolution and Taxonomic Significance of Seed Micromorphology in Impatiens (Balsaminaceae) - Song, Yong-Xiu; Peng, Shuai; Mutie, Fredrick Munyao; Jiang, Hui; Ren, Jing; Cong, Yi-Yan; Hu, Guang-Wan (Frontiers in Plant Science, 2022)
Impatiens is one of the most species-rich genera of angiosperms, with more than 1000 species distributed in Eurasia and Africa. Previous studies have shown that seeds of Impatiens display enormous morphological diversity and seed micromorphology may contribute to the classification of those species. However, the micromorphological seedcoat characteristics of Impatiens seeds have not been systematically studied. In this study, we examined 117 Impatiens seeds from two subgenera and seven sections, and analyzed the seed characters of shape, primary ornamentation, secondary ornamentation, anticlinal cell wall, and periclinal cell wall. We discovered that, according to the different shapes of ornamentation, seedcoat can be divided into three types, viz, reticulate type, protrusive type, appendicular type, and that they can be further subdivided into ten subtypes. In addition, the characteristics of seedcoat ornamentation with taxonomic significance in this genus are discussed. We reconstructed the ancestral states of the above seed characters of the Impatiens using the maximum likelihood approach, based on the reconstructed phylogenetic framework. The seed character reconstruction showed that the seed shape, primary ornamentation, and anticlinal cell wall could be identified as unambiguous, while other characters were ambiguous in the last common ancestor of Impatiens. Reconstruction of important seed morphological characters showed that the secondary ornamentation possesses high plasticity and the primary ornamentation has high homology. In addition, we inferred the evolutionary trends of seed ornamentation, and found that the seedcoat ornamentation of Impatiens experienced a complex evolutionary process from a reticulate type into more complex types. We also discussed the relationship between seedcoat diversity versus environmental adaptation and seed dispersal in Impatiens.